The Effect of Thin Capitalization, Institutional Ownership and Managerial Ownership on Tax Avoidance in Automotive Companies on the Indonesia Stock Exchange - Widyastuti Prihastiwi; Ariyani (NAROTAMA UNIVERSITY, Indonesia, 2023)
This study aims to examine the Effect of Thin Capitalization, Institutional Ownership and Managerial Ownership on Tax Avoidance in Automotive Companies on the Indonesia Stock Exchange. This study uses a quantitative approach. The samples used as objects in this study were automotive companies listed on the Indonesia Stock Exchange during the 2017 – 2021 period. The samples were selected using a purposive sampling method. The type of data used in this research is secondary data. The results of this study are that Thin capitalization has an effect on Tax Avoidance, Institutional Ownership has no effect on Tax Avoidance, Managerial Ownership has no effect on Tax Avoidance and Thin capitalization, Institutional Ownership and Institutional Ownership have a simultaneous effect on Tax Avoidance. Boundary problems in research are very important in bringing the subject matter closer so that there is no confusion in interpreting research results. In order for the research to be more focused and perfect, it is necessary to limit the variables in this research. Therefore, the authors limit only using the independent variables Thin Capitalization, Institutional Ownership and Managerial Ownership and the dependent variable tax avoidance, using secondary data on automotive companies on the Indonesia Stock Exchange from 2017 to 2021. This research is expected to provide motivation for companies to be aware of not doing tax evasion, and this research is expected to be useful for investors so they can be careful in choosing companies to invest their capital.